Crowd-sourced syllabus : a curriculum for resistance - McRae, Leanne (Bingley, U.K. : Emerald Publishing Limited, 2020)
Curating the contributions of Twitter users via hashtags, crowd-sourced syllabi respond to evolving crises and critical questions in real time, resulting in living materials for educators and students. This book showcases how these syllabi are filling a gap in educational efficacy by providing access to forgotten, hidden and unpopular resources.
Prelims -- Introduction an ultra-realist refusal -- 1 An education in crisis: economics, experts and enlightenment -- 2 The lads: a rebellious refusal of resilience -- 3 Disintermediating the archives: evental education -- 4 #Fergusonsyllabus -- 5 #Newfascismsyllabus -- 6 #Standingrocksyllabus -- 7 #Rapeculturesyllabus -- 8 #Sanctuarysyllabus -- 9 #Blackdisabledwomansyllabus -- Conclusion Popular provocations: #Lemonadesyllabus and #ColinKaepernicksyllabus -- Index.
Includes index.
Print version record.
Keywords: Curriculum planning; Educational technology; Education -- Curricula; Curriculum planning & development